Loan approval evaluation framework of public-private partnership project of battery storage power station under interval-valued intuitionistic fuzzy environment. (1st May 2020) - Geng, Shuai; Lin, Lijun; Yin, Yu; Yan, Hui
Abstract: The main objective of this paper is to propose a loan approval evaluation framework of public-private partnership project (PPP) of battery storage power station (BSPS) for the commercial bank to evaluate and select the optimal project to provide the loan and then promote the development of BSPS-PPP. In order to achieve this goal, this study proposed a loan approval evaluation index system which consist of 5 attributes, 14 criteria and 45 sub-criteria. The novelty of this loan evaluation index system is that it reflects the basic requirement of loan approval of the commercial bank based on the characteristics of BSPS and PPP project, the commercial banks can better prepare for possible risks of BSPS-PPP. The proposed decision model was established based on the interval-valued intuitionistic fuzzy value (IVIFV) and interval number. Its novelty is that ①The model not only satisfies the experts' expression habit of uncertainty, but also can be handled the uncertainty in the performance evaluation value and the criteria's weights properly; ②the proposed weight determining method based on the deviation maximization principle can not only maintain the will of decision makers as much as possible, but also decrease the uncertainty of weights. Finally, the effectiveness of loan approval evaluation framework was verified based on a case study of China. According to the application effect of the evaluation index system and the proposed model, 3 managerial implication are put forward. Highlights: Loan approval evaluation index system of PPP project of electrochemical storage power station. The interval value intuitionistic fuzzy value and interval number are used to handle with the uncertainty. The deviation maximization principle was used to decrease the uncertainty of criteria's weights.